The diagnostic value of immunohistochemically HBsAg staining patterns in chronic hepatitis B infection: correlation among histological, serological and immunohistochemical findings - Selçuk BİLGİ; İsmail ÇIRPAN; Kemal KUTLU; Sedat ÖZDEMİR; Gülbin DÖKMECİ (Turkish Journal of Gastroenterology, 2020)
-